2002
DOI: 10.1021/jp025580w
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Nature of SiH4−BH3Complex:  Theoretical Investigation of New Mechanistic Pathways Involving SiH3and BH4Radicals

Abstract: We have investigated a new type of interaction between silane (SiH4) and borane (BH3) using high level ab initio calculations. The SiH4−BH3 complex is found to be extremely stable with the formation of a bridged hydrogen bond between SiH4 and BH3. Hence, it might have a hitherto unknown role in the mechanism of chemical vapor deposition (CVD), which is employed in the fabrication of boron doped silicon semiconductor materials. In an attempt to unravel this role and the underlying reasons responsible for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…It has been suggested that electron correlation is important in describing the binding of these complexes and that the Hartree−Fock (HF) method fails to predict the correct structure for the SiH 4 •••BH 3 complex. 6 Usually, core electrons are excluded from the electron correlation calculations because most chemical phenomena involve only the valence electrons. Excluding the core electrons, that is, the frozen core approximation (FC), can save significant computational cost.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that electron correlation is important in describing the binding of these complexes and that the Hartree−Fock (HF) method fails to predict the correct structure for the SiH 4 •••BH 3 complex. 6 Usually, core electrons are excluded from the electron correlation calculations because most chemical phenomena involve only the valence electrons. Excluding the core electrons, that is, the frozen core approximation (FC), can save significant computational cost.…”
Section: Resultsmentioning
confidence: 99%
“…13 Nonetheless, structural characterization of unsupported Type II σ-complexes still remains an unmet challenge, despite the fact that they have long been perceived as key intermediates in σ-bond metathesis. 14 Intriguingly, theoretical studies by Kim 15 and Gordon 16 suggested that Lewis acid BH 3 could form Type II σ-complexes with SiH 4 in gas phase in which one of the H−Si bond is substantially activated. Recently Piers successfully isolated a borane-HSiEt 3 adduct with a borole derivative, 1,2,3-tris-(pentafluorophenyl)-4,5,6,7-tertafluoro-1-boraindene.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many studies have been carried out of precursor compounds used for chemical vapor deposition of boron‐doped silicon. Hu et al 20, 21. studied the reactions of SiH 4 and B 2 H 6 , and the interactions of SiH 4 and BH 3 .…”
mentioning
confidence: 99%